Efeito da interação de macrófagos co-cultivados com "Leishmania amazonensis" e bactérias no controle da infecção parasitária : Effect of the interaction of macrophages co-cultivated with "Leishmania amazonensis" and bacteria in the control of parasitary infection - Gallo-Francisco, Pedro Henrique, 1996- (2023)
Orientadores: Selma Giorgio, Marcelo Brocchi